Numerical experiments on radiative cooling and collapse in plasma focus operated in Krypton - Lee, S. (Springer US, 2013)
The Plasma Focus has wide-ranging applications due to its intense radiation of SXR, XR, electron and ion beams and fusion neutrons when operated in deuterium. The 5-phase Lee Model code has been developed for the focus operated in various gases including D, D–T, He, Ne, N, O, Ar, Kr and Xe. Radiation-coupled motion is included in the modelling. In this paper we look at the effect of radiation cooling and radiation collapse in krypton. The Pease–Braginskii current is that current flowing in a hydrogen pinch which is just large enough for the Bremsstrahlung to balance Joule heating. This radiation-cooled threshold current for a hydrogen pinch is 1.6 MA. It is known that in gases undergoing line radiation strongly the radiation-cooled threshold current is considerably lowered. We show that the equations of the Lee Model code may be used to compute this lowering. The code also shows the effect of radiation cooling leading to radiative collapse. Numerical experiments based on experimentally fitted model parameters are run to demonstrate a regime in which radiation collapse is observed in Kr at a pinch current of 50–100 kA.